Intracutaneous ALA photodynamic therapy - Tannous, Zeina (2011)
Background Photodynamic therapy (PDT) using topical aminolevulinic acid (ALA) depends on local drug uptake, metabolism to porphyrins, and depth of light penetration using different wavelengths. Topical ALA-PDT has limited depth of drug penetration. We studied induced porphyrin distribution and PDT after intradermal ALA administration using different drug concentrations followed by high-fluence red light irradiation. Materials and Methods Intradermal injections (∼2 mm deep) of ALA concentrations from 0.0005% to 1% were studied in swine to evaluated porphyrin fluorescence before PDT and clinical and histological damage 24 hours after PDT. Porphyrin accumulation was measured by fluorescence microscopy of frozen section. PDT was performed 3 hours after intradermal injections using a 635 nm LED array at a fluence of 200 J/cm2. Skin responses to PDT were observed grossly and by histology (blind evaluation). Results Intradermal ALA caused porphyrin accumulation in epidermis, hair follicles (HF), sebaceous glands (SG), sweat glands (eccrine glands, EG and apocrine glands, AG), and subcutaneous fat. Significant differences of fluorescence intensity were observed between different skin structures (P < 0.05), but there was no significant difference comparing HF to SG; epidermis with either HF or SG; and dermis with fat (P > 0.05). Intradermal ALA is potent. ALA concentrations ≥0.25% followed by red light exposures caused a very intense vascular PDT reaction. Moderate doses of injected ALA concentration (∼0.06%), selectively targeted EG. Low doses (≤0.016%) targeted fat; producing fat necrosis with minimal inflammation, manifested both clinically and histologically. In contrast to topical ALA-PDT, intradermal ALA-PDT can effectively photosensitize deep skin structures. Conclusion Potentially, intradermal ALA-PDT using various ALA concentrations may be useful for treating vascular lesions (malformations, hemangiomas, tumors), EG/AG disorders, fat or deep targets in skin. Lasers Surg. Med. 43:621–631, 2011. © 2011 Wiley-Liss, Inc.